Case management for high-cost Medicare beneficiaries. - Schore, Jennifer L.; Brown, Randall S.; Cheh, Valerie A. (Health Care Financing Review)
Part of a special section on ambulatory and community-based health-care services. A study was conducted to investigate the effectiveness of three Health Care Financing-funded case management demonstrations for high-cost Medicare beneficiaries in the fee-for-service sector. Data were drawn from Medicare claims files, from which measures were constructed of clients' service use and Medicare payments for these services during the year after they enrolled. The findings reveal that none of the demonstrations reduced Medicare spending and that none of them improved self-care or health. It is concluded that case management might be cost-effective if it is more well-defined and goal-oriented, incorporates financial incentives to generate savings in Medicare costs, and includes greater physician involvement.